2020
DOI: 10.32347/2410-2547.2020.104.117-135
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of impact of injury measures on the protection screens of combat armoured vehicles

Abstract: In order to evaluate the relative properties of the protective screen to the striking energy of the means of defeat, an experimental study was conducted, which allowed to test the hypothesis regarding the protection of the combat armoured vehicles against the means of defeat which, under the action of kinetic energy, destroy the armoured obstacle. Based on the data obtained during the experimental study, a mathematical model was constructed that describes the punching momentum of the protective screen. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Thus, the results of numerical simulation show that the preheating of the turbine blades of GTE with cooling channels can provide conditions for their thermal pulse cleaning. Further studies of this process should be carried out experimentally, according to the methodology that is determined in the studies [15,16]. Based on the numerical study of combustion process with heat exchange with the walls of the channel, it has been shown that for the dimensions of the channel characteristic of the cooling channels of turbine blades of GTE, thermo impulse cleaning is possible when the temperature of parts is from 500°C to 700°C, which is significantly below the operating temperature of the methods used at the present stage for this purpose.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Thus, the results of numerical simulation show that the preheating of the turbine blades of GTE with cooling channels can provide conditions for their thermal pulse cleaning. Further studies of this process should be carried out experimentally, according to the methodology that is determined in the studies [15,16]. Based on the numerical study of combustion process with heat exchange with the walls of the channel, it has been shown that for the dimensions of the channel characteristic of the cooling channels of turbine blades of GTE, thermo impulse cleaning is possible when the temperature of parts is from 500°C to 700°C, which is significantly below the operating temperature of the methods used at the present stage for this purpose.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Based on this analysis, a variant of classification of such devices is proposed and attention is focused on the need to study the experience of their use. An in-depth study of this problem is reflected in the study [10], in which an experimental study was conducted to assess the relative properties of the protective screen to the damaging energy of the munitions, which allowed to test the hypothesis put forward regarding the use of several layers of materials in protective screens to protect armored vehicles from munitions that destroy the armored barrier under the action of kinetic energy. Based on the experimental data obtained, a mathematical model was built that describes the pulse of penetration of the proposed armored barrier.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…In the study of such a system on the basis of a deterministic approach, when the mechanism of all phenomena is investigated, the process theory is used, on the basis of which the system is given by a strictly deterministic model, usually in the form of differential equations. [10].…”
Section: Presenting Main Materialmentioning
confidence: 99%
See 1 more Smart Citation
“…В роботі [2] розглянуто методичний апарат оцінювання оперативно-тактичних вимог до системи відновлення та визначення їх відповідності вимогам більш вищого рівня ієрархії із застосуванням теорії складних систем. В роботах [3][4][5]…”
Section: аналіз останніх досліджень та публікаційunclassified